2020
DOI: 10.1021/acs.jchemed.0c00732
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Directed Workshop for Developing Advanced Data Processing and Analysis Skills in Chemistry Using Microsoft Excel

Abstract: Data-handling, processing, and analysis skills are an integral part of a chemist's skill set and, more generally, are highly sought by employers. We report a self-directed workshop to develop and advance these key skills using the popular spreadsheet program Microsoft Excel. Making use of its accessible user interface, various contextualized problems relevant to chemistry are introduced, linking theory to practical applications and providing insight and understanding of processes that operate behind-the-scenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…With the rapid development of vocational education in our country, higher vocational colleges have trained millions of full-time graduates, provided tens of thousands of specialized technical personnel for the development of socialist society, promoted social progress, and accelerated the development of the economy has also solved the current situation of the shortage of technical talents in our country, so as to make the growth of talents meet the actual needs of the rapid social development and play an important role in improving social productivity and labor level [1].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of vocational education in our country, higher vocational colleges have trained millions of full-time graduates, provided tens of thousands of specialized technical personnel for the development of socialist society, promoted social progress, and accelerated the development of the economy has also solved the current situation of the shortage of technical talents in our country, so as to make the growth of talents meet the actual needs of the rapid social development and play an important role in improving social productivity and labor level [1].…”
Section: Introductionmentioning
confidence: 99%
“…With recent developments in information technology, we have provided computational science capabilities and materials informatics capabilities: These basics can be demonstrated with well-known software such as Gaussian program package and Microsoft Excel. While there have been many excellent physical chemistry laboratory courses that deal with experiments, , calculations, , and data science independently, we are not aware of any course that makes a strong connection among them. We hope that undergraduate chemistry students will have the means to acquire comprehensive knowledge of physical chemistry through our redesigned course.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Moreover, in the emergency context of the COVID-19 pandemic, computer-based chemistry education has been rapidly applied to online teaching. For example, Blackboard Collaborate virtual classroom package was used for online lab demonstration; 11 Microsoft Excel was used in data-handling, processing, and analysis; 12 augmented reality application was used in the demonstration of atomic stacking and lattice; 13 WebVR software such as Uptale was used to create the virtual crime scene for the educational situation; 14 embedded video questions were used for online assignments. 15 For teaching complexometric titration online, computer simulations can not only generate dynamic changing graphs, attract students' attention, and facilitate students' intuitive understanding but also generate corresponding results immediately according to the parameters selected by students.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies have shown that computer simulation and visual teaching methods can present knowledge more directly, concretely, and conveniently than traditional teaching methods. Other studies have shown that computer-based teaching is conducive to students’ inquiry-based learning , and independent learning, which may improve students’ academic level. , Moreover, in the emergency context of the COVID-19 pandemic, computer-based chemistry education has been rapidly applied to online teaching. For example, Blackboard Collaborate virtual classroom package was used for online lab demonstration; Microsoft Excel was used in data-handling, processing, and analysis; augmented reality application was used in the demonstration of atomic stacking and lattice; WebVR software such as Uptale was used to create the virtual crime scene for the educational situation; embedded video questions were used for online assignments…”
Section: Introductionmentioning
confidence: 99%